The Impact of Strategic Performance on Job Satisfaction in Private Placement Companies - Hattab Almaliki, Helen Neamah; Mohammed Kareem, Jasim; Al-Soltane, Ali Isam; Mousa Sabti, Yousif; Salman Kadhim, Arshad (South Asian Journal of Social Sciences and Humanities, 2023)
This research aims to know the success of strategic performance on job satisfaction in private placement companies in Malaysia and to clarify the role of senior performance in the actual implementation of the strategy of the private placement companies (PPC). The research uses 114 PPC from 2010 to 2020 by using OLS regression. The main hypothesis, which is the existence of a strategic performance relationship with job satisfaction. To follow up on the phenomenon of research, recording and analysing data to draw results and test research hypotheses. Which results showed a positive and statistically significant relationship between strategic performances on job satisfaction. The research reached many results, the most important of which is the proper application of strategic performance that leads to the success of the PPC. The necessity of developing a marketing strategy based on the analysis of the internal and external environment. It meets the needs of workers and customers, as well as recommendations, the most important of which is the need to apply modern strategic performance in PPC, the need to motivate workers and evaluate their performance.